2022
DOI: 10.3390/jcm11030683
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of the Pilates Method in Patients with Multiple Sclerosis: A Systematic Review

Abstract: The Pilates Method is a rehabilitation tool with verified benefits in pain management, physical function, and quality of life in many different physiotherapy areas. It could be beneficial for patients with multiple sclerosis (pwMS). The aim of the study was to summarize current evidence for the effectiveness of Pilates in pwMS. A comprehensive search of Cinahl, Scopus, Web of Science, PEDro, and PubMed (including PubMed Central and Medline) was conducted to examine randomized controlled trials (RCT) that inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 53 publications
2
8
0
1
Order By: Relevance
“…Some of the results of this review are consistent with the results of other recently published systematic reviews examining the therapeutic effects of PE/PEG in relieving patients with multiple sclerosis. [ 59 , 60 ] This study showed that PE/PEG was beneficial for patients with multiple sclerosis; however, the quality of the included studies was low and the risk of bias of the included trials was not analyzed. Meanwhile, we found that PE/PEG was a better intervention for the middle-aged and elderly female population, and our study concluded that the longer the duration of Pilates training, the better the effect.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the results of this review are consistent with the results of other recently published systematic reviews examining the therapeutic effects of PE/PEG in relieving patients with multiple sclerosis. [ 59 , 60 ] This study showed that PE/PEG was beneficial for patients with multiple sclerosis; however, the quality of the included studies was low and the risk of bias of the included trials was not analyzed. Meanwhile, we found that PE/PEG was a better intervention for the middle-aged and elderly female population, and our study concluded that the longer the duration of Pilates training, the better the effect.…”
Section: Discussionmentioning
confidence: 99%
“…Mokhtarzarde et al [ 18 ], analyzing a limited number of papers, concluded that the scientific literature did not support the positive effects of PA in pwMS. A recent review that analyzed the effects of Pilates in patients with MS underlined its role in improving BC, muscle strength, and core stability [ 37 ]. Ewanchuk and colleagues conducted a scoping review investigating the effects of PA on vascular comorbidities in pwMS.…”
Section: Discussionmentioning
confidence: 99%
“…Among the other benefits (i.e., feasibility, well tolerability, mood, etc. ), a general reduction in BMI and %F has been reported in pwMS following specific physical exercises, such as general PA [ 36 ], Pilates [ 37 ], and aerobic training [ 38 ]. Additionally, some studies focused on D interventions reported an improvement in BC [ 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies demonstrate favorable outcomes following Pilates training interventions, indicating its safety and effectiveness in addressing various aspects of dysfunction, including balance, strength, quality of life, cognition, physical performance, walking, and posture parameters in individuals with MS [10]. Reports indicate high adherence rates and minimal adverse effects associated with Pilates interventions [11].…”
Section: Description Of the State Of Knowledgementioning
confidence: 99%